Faro Mine Records: Archival Work in Extractive Projects - Carlin, Isabel (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
The Faro mine was a large resource extraction project in central Yukon that operated from 1969 to 1998. Despite its historic relevance to the world economy and significant contemporary research interest, the Faro mine’s records (which at closure were contained in approximately 1,800 banker’s boxes) are not well understood due to a lack of capacity to process this volume of records and complex issues regarding the application of archival theory. This article provides an overview of the hundreds of thousands of records produced by and at the Faro mine, includes a history of their creation, and uses this case study to investigate the application of archival theories of provenance, respect des fonds, and creatorship. The difficulty of applying these theories to the Faro mine records reflects a broader complexity regarding ownership and accountability in major resource extraction projects. The article concludes that the resulting lack of access to mine records hinders transparency and historical research and that further archival work is needed to ensure adequate records management in future projects.